2017
DOI: 10.1007/s00415-017-8682-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind, placebo-controlled, cross-over trial (Vestparoxy) of the treatment of vestibular paroxysmia with oxcarbazepine

Abstract: ObjectiveVestibular paroxysmia (VP) is characterized by short, often oligosymptomatic attacks of vertigo which occur spontaneously or are sometimes provoked by turning the head. Despite the description of the disease almost 40 years ago (first termed “disabling positional vertigo”), no controlled treatment trial has been published to date. The Vestparoxy trial was designed as a randomized, placebo-controlled, double-blind cross-over trial to examine the therapeutic effect of oxcarbazepine (OXA) in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
0
11
0
3
Order By: Relevance
“…For the latter reason, MRI in this condition is indicated mainly to rule out other etiologies. A randomized, controlled trial demonstrated the significant therapeutic efficacy of oxcarbazepine at a dosage of 900 mg/day (attack frequency halved), although poor tolerability of the drug led to a 60% dropout rate (25). Lac osamide (100-200 mg/day) seems to be a welltolerated alternative, as individual cases of off-label use have shown (26).…”
Section: Vestibular Paroxysmiamentioning
confidence: 99%
“…For the latter reason, MRI in this condition is indicated mainly to rule out other etiologies. A randomized, controlled trial demonstrated the significant therapeutic efficacy of oxcarbazepine at a dosage of 900 mg/day (attack frequency halved), although poor tolerability of the drug led to a 60% dropout rate (25). Lac osamide (100-200 mg/day) seems to be a welltolerated alternative, as individual cases of off-label use have shown (26).…”
Section: Vestibular Paroxysmiamentioning
confidence: 99%
“…or oxcarbazepine 300–900 mg p.o. per day) reduces the ephaptic transmission and thus results in a significant reduction of both attack frequency and severity within a few days or weeks 110 , as shown in a double-blind randomized controlled clinical trial for oxcarbazepine versus placebo 122 . It should, however, be noted that there was a high drop-out rate due to adverse effects in this study.…”
Section: Episodic Vestibular Syndromesmentioning
confidence: 89%
“…Eine Therapie mit Natriumkanalblockern (Carbamazepin 200–800 mg oder Oxcarbazepin 300–900 mg pro Tag) reduziert die ephaptischen Entladungen und führt innerhalb weniger Tage bis Wochen meist zu einer deutlichen Reduktion von Attackenfrequenz und –schwere 110 , wie in einer doppelblind randomisierten kontrollierten Studie für Oxcarbazepin gegen Placebo gezeigt wurde 122 . Allerdings brachen viele Patienten aufgrund von Nebenwirkungen die Studie vorzeitig ab.…”
Section: 116 Therapieunclassified
“…41 It may be triggered by exercise or heat, is associated with 'staccato' or 'type-writer' tinnitus and is often responsive to carbamazepine or oxcarbazepine. 42,43 Syndrome 4: imbalance Imbalance is the final common vestibular syndrome and can be caused by numerous conditions spanning across systems.…”
Section: Vestibular Migrainementioning
confidence: 99%